Prevalence of violence towards men living with HIV/AIDS in rural communities of SouthWestern Uganda - Kakooza, Javilla Kamya; Nampijja, Ritah; Kwagala, Faith; Nuwabasa, Flavia; Mpuuga, Owen; Isiagi, Gomer; Rukundo, Godfrey Zari (African Health Sciences, 2022)
Violence towards HIV positive men is one of the silent barriers to utilization of HIV care services. HIV positive men are potential victims of violence from other people including women, and violence may interfere with treatment outcomes. This study determined the prevalence of violence towards HIV positive men in rural communities of southwestern Uganda. Methods: A cross-sectional study was conducted among 307 HIV positive men at selected health centers using an interviewer administered questionnaire. Data were analyzed in SPSS version 23 using chi-square and multivariate regression at 95% level of significance and a precision of 0.05. Of the 307 participants, 45.3% had experienced violence. Of these, 23.8% (n=73) had experienced kicking or slapping while 12.7% (39) reported sexual violence. Factors associated with violence were; using alcohol and drugs (aOR 0.26, 95% CI 0.09-0.76, p=0.014), knowledge of support structures (OR 2.25, 95% CI 1.33-3.78, p=0.002) and owning land for farming (aOR 0.26, 95% CI 0.10-0.70, p=0.011). The prevalence of violence at 45.3% is quite high especially since violence against men is rarely talked about. This should not be ignored there should be strategies to support this vulnerable group.
Keywords: HIV positive men; Violence; Prevalence; Rural communities